Efektivitas Pemberian Tambahan Penghasilan Pegawai Dalam Meningkatkan Kinerja Pegawai di Sekretariat Daerah Kabupaten Tojo Una-Una - Adri Reza Engka; Nawawi Natsir; Nuraisyah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Generally, the research purpose is to know how the effectiveness of giving additional employe income for increase the employee performance working at Regional Secretary, Tojo Una-Una Regency and also to find out some elements which influenced it. This research uses descriptive research method that the research is done by the real living rule which describe and explain it as accurately and systematically of the effectiveness of giving additional employe income for increase the employee performance working at Regional Secretary, Tojo Una-Una Regency. The research also use qualitative research refers to effectivity theory by Richards M. Steers (1980:193) consist of three indicators: purpose optimalization, System Perspective, and Behaviour Emphasizing. Furthermore, to know about the element that influence the efectivity, use theory of Richard M.Steers (1999: 159), which has four indicators that Organization Characteristic, Environment Characteristic, Working Charcteristic and Policy Characteristic, and Mangement Pactice. The result of research show that there are some effectiveness elements have less achiement that’s on behavior emphazing and also there are some elements has less influenced that policy characteristic and management practice.